Rare bird documentation form for Lesser Black-backed Gull at Greencastle Road at Coralville Reservoir, 1993 - Fuller, James Let al (1993)
Rare bird documentation form for a Lesser Black-backed Gull at Greencastle Road at Coralville Reservoir in Johnson County, IA on December 19, 1993. Epson - sheet feed